PARENTHOOD AND LABOUR MARKET OUTCOMES IN SERBIA - Lebedinski, Lara; Vladisavljević, Marko (Economic Annals, 2022)
Using the Labour Force Survey data for the period 2014 to 2018 for Serbia, this paper explores the effect of parenthood on the labour market trajectories of parents, the so-called ‘parenthood penalty’. We find that mothers are less likely than non-mothers to be active in the labour market when their children are very young, but this effect is transitory, and mothers of older children are actually more likely to be active than non-mothers. Similarly, we observe that mothers of small children are less like-ly to work overtime than non-mothers, but also that both parents of older children are more likely to engage in overtime work than men and women without children. We find a motherhood penalty in terms of hourly wages for mothers with younger children, but the penalty is not significant as children become older. By contrast, fathers are more likely to be active than non-fathers. We do not find an effect of fatherhood on hours worked or hourly wages. Overall, our results suggest that the motherhood penalty is present in Serbia in the early stages when children are young, but motherhood does not seem to have lasting effects on the labour market participation, hours worked, or wage rates of mothers. We do not find evidence of a fatherhood bonus, but we find that fathers are more likely to be active than non-fathers.